Metabolic Syndrome and Aging: Calcium Signaling as Common Regulator - Soprano, Maria; Rusciano, Maria R.; Ciccarelli, Michele; Serena Maione, Angela; Formisano, Pietro; Illario, Maddalena (Current Diabetes Reviews, 2016)
Aging is one of the most important societal challenges that western societies face, as a result of longer life expectancy and reduced natality rates. Aging is a success story of our health and social systems, but raises sustainability issues that are linked to the increased need for services of older adults, due to the reduction of their independence and to the co-existence of multiple chronic diseases. The metabolic syndrome can be considered an age-related disease, since its prevalence increases with age. Current demographic trends in the population highlight aging-related dysfunctions that contribute to the onset of several metabolic diseases, and the need for innovative, effective and sustainable approaches. This review describes the correlation between the metabolic syndrome and aging, and the underlying common molecular mechanisms, focusing on calcium signaling and its crosstalks.
Keywords: Aging